Concentração de poder e acurácia das previsões dos analistas de mercado de capitais - Pessanha, José Reinaldo (2012)
Analysts are essential to the functioning of capital markets as they make predictions and recommendations that support the investment decisions of both institutions and individual investors. Analysts study the fundamentals of public companies, their growth prospects, financial structure and cash flow, corporate governance, industry structure and the macroeconomic environment in which companies are inserted. In this context, business leaders play a major role, as they influence the directions of the corporation and their performance. The goal of this paper is to investigate the influence of the concentration of power in the hands of the major corporate leader on the accuracy of analyst earnings forecasts of Brazilian companies. The accuracy is measured in accordance with the international literature. The proxy for the concentration of power was constructed by Silveira and Barros (2011b) and takes into consideration the individual power of the main corporate leader the Chairman of the Board of Directors (Chairman) or the CEO (Chief Executive Officer) and also the degree of passivity and homogeneity of the Board of Directors. The sample contains 107 public companies listed in BM&FBOVESPA (Bolsa de Valores de São Paulo) in 2010. It only includes companies that had analyst coverage in the twelve months preceding the end of the fiscal year. The forecasts and financial information were collected from Thomson One Analytics® and Economática®. Information on the concentration of power was provided by Silveira and Barros (2011b), who collected the data in the websites of companies and in Comissão de Valores Mobiliários (CVM). The analysis shows evidence that the concentration of power positively influences the accuracy of analyst forecasts. This idea is in line with a few prior studies on the concentration of power and volatility of results that argue that powerful business leaders tend to be more conservative.